Impact assessment of green infrastructure and urban growth on stormwater runoff through geospatial modeling - Agnes Liji George; Pramod Kumar; Kshama Gupta (Frontiers in Water)
Kochi city in southern India periodically experiences waterlogging or urban floods due to unabated urban growth and extreme rainfall events. This study aims to mitigate urban flood hazards through green infrastructure (GI) and its effective management. Assessment of storm water runoff (SWR) modeling is carried out in four scenarios, viz., baseline, past, severe, and green, using urban growth and GI driven simulations. Urban growth modeling and GI suitability analysis are carried out using Cellular Automata Markov (CA-Markov) and urban planning guidelines, respectively. The study provides insights into how GI influences SWR reduction and urban environment conservation, with 16% SWR reduction as compared to the baseline scenario and 18% when compared to the severe scenario.